Educational Stewardship: Cultivating Career Excellence and Professionalism for Teachers - Lila Maria Kaban; Rifin Khong; Erina Alimin (Universitas Pendidikan Ganesha, 2024)
Teachers face significant challenges in career development, including lack of vision, excessive workload, inadequate professional development, and long hours coupled with administrative tasks. This community service project applies the concept of service learning to improve teachers' professional knowledge and career planning. The initiative, implemented in March 2024 at the Pride Education Foundation in Pematangsiantar, North Sumatra, includes seminars and training sessions designed to equip educators with innovative teaching strategies, effective classroom management techniques, and methods to foster a positive learning environment. The program uses seminars, mentoring, and interactive discussions to deliver its content. Evaluative measures, including pre- and post-seminar assessments and participant feedback, were used to measure the impact of activities on teachers' professional growth. The results of the evaluation show that community service initiatives significantly support teachers in career planning and increase their teaching knowledge. These findings underscore the value of such initiatives in advancing educators' professional development, enhancing their ability to meet diverse student needs and navigate educational challenges. It is recommended that schools implement regular evaluations and closely monitor teacher career development to maintain and develop these achievements.